ISSUES OF UNIVERSAL HUMAN VALUES AND SPIRITUAL AND MORAL EDUCATION IN EASTERN PHILOSOPHY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the development of socio-philosophical thought among the peoples of the East, with a particular focus on Central Asia. It critically examines the Eurocentric tendencies in Western philosophical literature that historically marginalized Eastern philosophical contributions. The paper highlights the rich intellectual heritage of Eastern civilizations, including Chinese Confucianism and Islamic philosophy, and emphasizes their significant impact on global philosophical and scientific progress. Prominent thinkers such as Confucius, Lao Tzu, Ibn Khaldun, and others are discussed for their contributions to ethics, education, and socio-political thought. The decline of the first Renaissance in Central Asia due to Mongol invasions and the transition from rationalism to mysticism in Islamic philosophy are also analyzed. The article concludes by calling for a more balanced and inclusive understanding of the shared intellectual history of humanity.